(untitled) (Journal of Forensic Medicine & Toxicology, 2026)
Introduction: Age estimation can be done from early physiological changes in the body, teeth development and radiological examination of ossification centres. Methodology: It is a Cross sectional, mortuary-based study carried out on the dead bodies of 70 subjects brought for Medicolegal Autopsy to Mortuary, Department of Forensic Medicine & Toxicology, All India Institute of Medical Sciences, New Delhi. This study included peoples age between 1-18 years with known supportive documents like AADHAR, other ID & also personal interaction with legally accepted represen tatives (LAR). Both Antero-Posterior (AP) and lateral views of X-rays of the left Elbow and Wrist joints were taken. Results & Discussion: All the X-rays were analysed focusing on the epiphyseal union in these two joints. Total 70 people participated in the study, out of which 41 are male and 29 are female. In males, the ossifi cation centres around Wrist joint completely fuse earliest at 15 years whereas in females, the ossification centres around Wrist joint completely fuse earliest at the age of 14 years. Complete fusion of distal end of Radius and Ulna has occurred 1 year earlier in females, as compared to males. Mean age for complete fusion of distal end of Radius in female subjects is 17.0±1.25 years and mean age for the same in male subjects is 16.89±1.27 years, while mean age for complete fusion of distal end of Ulna in female subjects is 16.57±1.40years and mean age for the same in male subjects is 16.75±1.28 years. It has also been observed that Carpal bones are not appearing in any particular order. Conclusion: Total sample size for the study is not large enough, to make proper inferences regarding the ossi fication of joints. Tanner-Whitehouse method and Greulich-Pyle method should be modified as applicable to Indian population to make more scientific assessment about ossification status of the joints